Characteristics of Intracerebral Hemorrhage at Dr. Kariadi General Hospital: A Serial Case - Nadhira Faizah Putri Priambodo; Kayana Zahra Kallista Rambey; Amira Cinta Maharani; Diah Satyaningrum; Nuzulur Rakhmah Nurulyana; Gibran Chandra Syarif Hidayatullah; Maria Belladonna Rahmawati Sugianto; Santoso Jaeri (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Stroke is an acute neurological deficit caused by sudden or rapid disruption of blood circulation to the brain. Intracerebral hemorrhage is the subtype of stroke with the highest mortality and disability rate. Several risk factors may be related to the clinical outcome of intracerebral hemorrhage. Herewith we present a case series regarding the characteristics of intracerebral hemorrhage. Methods: A case series among three intracerebral hemorrhage cases in January - February 2024 at Dr. Kariadi Hospital. Epidemiological, and clinical data were recorded and reported. Case Presentations: Three cases were studied, the main complaint of the patient was decreased consciousness. These patients had different risk factors for stroke. According to the Siriraj score, NIHSS score, and neuroimaging findings, these patients had hemorrhagic strokes with different brain lesions. Two-thirds of the patients had uncontrolled hypertension and one patient was accompanied by uncontrolled diabetes mellitus. Conclusion: Overall, all patients were >45 years old and the risk factors of these patients were modified risk factors that is uncontrolled hypertension and diabetes mellitus over a long period resulting in ganglionic hemorrhage.